THE EFFECT OF AERODYNAMIC DESIGN ON FUEL EFFICIENCY IN COMMERCIAL VEHICLES - Carlos Fernandez; Siti Shofiah; Ardi Azhar Nampira (Journal of Moeslim Research Technik, 2025)
The increasing demand for fuel efficiency in commercial vehicles has prompted extensive research into aerodynamic designs. Improved aerodynamics can significantly reduce drag, leading to enhanced fuel economy and lower operational costs for commercial fleets. Understanding the relationship between aerodynamic design and fuel efficiency is critical for optimizing vehicle performance. This research aims to evaluate the impact of various aerodynamic designs on the fuel efficiency of commercial vehicles. The study focuses on analyzing the performance differences between conventional and streamlined vehicle shapes. An experimental approach was employed, utilizing computational fluid dynamics (CFD) simulations alongside real-world driving tests. Several vehicle models with different aerodynamic features were tested under controlled conditions. Fuel consumption data was collected and analyzed to assess the relationship between design modifications and fuel efficiency. The findings indicated that streamlined designs improved fuel efficiency by an average of 15% compared to conventional models. Vehicles with enhanced aerodynamic features experienced reduced drag coefficients, leading to significant fuel savings during operation. The results demonstrated a clear correlation between aerodynamic optimization and improved fuel economy. The research highlights the crucial role of aerodynamic design in enhancing fuel efficiency for commercial vehicles. These findings emphasize the importance of integrating aerodynamic considerations into vehicle design processes.